Frequency and distribution of patellar luxation in dogs - Alam, M. R.; Lee, J. I.; Kang, H. S.; Kim, I. S.; Park, S. Y.; Lee, K. C.; Kim, N. S. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
This study investigated the frequency and distribution of patellar luxation in the dogs presented to the Chonbuk National University Animal Medical Centre during January 2000 to September 2005. Patellar luxations were classified as medial or lateral, and unilateral or bilateral, were graded I to IV, and were subdivided according to age, sex and size of the dogs. The incidence of medial patellar luxation (MPL) was greater than the incidence of lateral patellar luxation (LPL) in both small and large dogs. Small-breed dogs were admitted almost exclusively with MPL. LPL was found uncommon; however it was observed more often in larger-breed dogs. Surgical correction was performed primarily in the dogs (165 stifles in 111 dogs) with grade II, III and IV patellar luxations following different surgical techniques. The combination of the surgical techniques was found to be more effective for the management of the disease. The prognosis was found to be favourable, because when the grade was low, the dog was younger, without cruciate ligament rupture, and as the surgical correction was performed with combination of more techniques.
Keywords: Medial patellar luxation; lateral patellar luxation; dog